Acute-onset postoperative endophthalmitis after cataract surgery performed by resident and attending physicians at a university teaching hospital. Issue 11 (November 2022) - Kunkler, Anne L.; Sengillo, Jesse D.; Al-Khersan, Hasenin; Fan, Kenneth C.; Laura, Diana M.; Miller, Darlene; Donaldson, Kendall E.; Yoo, Sonia H.; Yannuzzi, Nicolas A.; Sridhar, Jayanth; Gedde, Steven J.; Smiddy, William E.; et al.
Abstract : This retrospective series found the rate of endophthalmitis after cataract surgery to be 0.09% in resident-performed cases and 0.06% in attending-performed cases, but this difference was not statistically significant. Abstract : Purpose: To evaluate acute-onset postoperative endophthalmitis following cataract surgery and to compare rates between resident and attending physician-performed cohorts. Setting: Bascom Palmer Eye Institute, Miami, Florida. Design: Retrospective chart review. Methods: Records of patients diagnosed with endophthalmitis within 6 weeks of surgery performed by attending and resident physicians between January 1, 2015, and December 31, 2020, were reviewed. Total cataract volume was obtained from institutional records, and resident case totals were obtained from case logs. Endophthalmitis cases were obtained from billing records and confirmed with chart review. Results: There were 22 cases of endophthalmitis among 32 505 cases (0.068%). Endophthalmitis occurred in 6 of 6447 (0.093%) resident cases and 16 of 26 058 (0.061%) attending cases ( P = .55). The most common bacterial isolates were coagulase-negative Staphylococcus (8/22, 36.3%) and Streptococcus species (3/22, 13.6%), with negative cultures in 10 (10/22, 45.5%). Initial treatment with vitreous tap and injection of intravitreal antibiotics was performed in 21 eyes (21/22, 95.4%) and vitrectomy with intravitreal antibiotic injection in one (1/22, 4.5%). Vitrectomy was performed secondarily in 9 patients (9/22, 40.9%). Corrected distance visual acuity (CDVA) at last follow-up was ≥20/40 in 13 eyes (13/22, 59%) and ≤hand motions in 3 eyes (3/22, 13.6%). CDVA (logMAR mean ± SD) was 1.22 ± 1.16 in resident and 0.49 ± 0.79 in attending cases ( P = .11). Conclusions: In the current study, acute-onset postoperative endophthalmitis developed infrequently following cataract surgery. The rates and visual outcomes of endophthalmitis were similar in resident and attending cases.